Butterfly diversity as a data base for the development plan of Butterfly Garden at Bosscha Observatory, Lembang, West Java (Biodiversitas Journal of Biological Diversity, 2009)
Subahar TSS, Yuliana A (2010) Butterfly diversity as a data base for the development plan of Butterfly Garden at Bosscha Observatory, Lembang, West Java. Biodiversitas 11: 24-28. Change of land use and the increasing number of visitors to Bosscha area was one factor for the development plan of butterfly garden in the area. The objectives of this research were to examine butterfly diversity and its potential for development plan of butterfly garden. Butterfly diversity and its richness conducted by standard walk methods. Host plantand larval food plant was recorded during butterfly survey. Public perception on the development plan of butterfly garden was examined by questionnaire. The results showed that 26 species of butterfly was found in Bosscha area and Delias belisama belisama was the most dominant species. Public perceptions consider that the development plan of butterfly garden will give benefit to the community; not only providing new insight (40.41%), additional tourism object (23.97%) and will gave aesthetical value (17.12%). Twelve local speciesshould be considered for development plan of butterfly garden: Papilio agamemnon, P. demoleus, P. memnon, P. sarpedon, Delias belisama, Eurema hecabe, Danaus chrysippus, Argynnis hyperbius, Cethosia penthesilea, Hypolimnas misippus, Melanitis phedima and Euthalia adonia. Host plant: Bougainvillea spectabilis, Citrus aurantium, Lantana camara, Macaranga tanarius and food plants: Citrus aurantium, Cosmos caudatus, Eupatorium inulifolium, Gomphrena globosa, Hibiscus rosa-sinensis, Lantana camara, and Tithonia diversifolia.Key words: host plant, butterfly diversity, Bosscha Observatory, standard walk.